2020
DOI: 10.2196/19713
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Utilization and Perception of an Artificial Intelligence–Based Symptom Assessment and Advice Technology in a British Primary Care Waiting Room: Exploratory Pilot Study

Abstract: Background When someone needs to know whether and when to seek medical attention, there are a range of options to consider. Each will have consequences for the individual (primarily considering trust, convenience, usefulness, and opportunity costs) and for the wider health system (affecting clinical throughput, cost, and system efficiency). Digital symptom assessment technologies that leverage artificial intelligence may help patients navigate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
85
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(96 citation statements)
references
References 26 publications
9
85
1
1
Order By: Relevance
“…Research supported by Ada Health GmbH shows that Ada had the highest top 3 suggestion diagnostic accuracy (70.5%) compared to other SCs [ 19 ], and the correct condition was among the first three results in 83% in an Australian assessment study [ 20 ]. Similarly to our results, the majority of patients would recommend Ada (85.3%) to friends or relatives [ 21 ].…”
Section: Discussionsupporting
confidence: 89%
“…Research supported by Ada Health GmbH shows that Ada had the highest top 3 suggestion diagnostic accuracy (70.5%) compared to other SCs [ 19 ], and the correct condition was among the first three results in 83% in an Australian assessment study [ 20 ]. Similarly to our results, the majority of patients would recommend Ada (85.3%) to friends or relatives [ 21 ].…”
Section: Discussionsupporting
confidence: 89%
“…Most of the patients in that study (274/304, 90.1%) reported receiving useful information for their health problems and reported that they would use the symptom checker again (278/304, 91.4%) [ 14 ]. These findings are in line with another study that examined perspectives on use of the “Ada” symptom checker, which showed that most of the participants (443/503, 88.1%) would recommend the platform to a relative [ 16 ]. An important factor that seems to influence symptom checker acceptance is age, with younger populations exhibiting higher acceptance [ 14 , 15 ].…”
Section: Introductionsupporting
confidence: 88%
“…However, handover to HCPs was not carried out in their study, nor did the tool have a system to enable handover. A number of studies 9,20,21 have reported apps for self-assessment of urgency/triage in the general practice and acute primary care setting, but evaluation of the handover of history and symptom information to HCPs was not addressed.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study found that patients using Ada's tool in a primary care waiting room found it helpful and easy to use. 9 If appropriately adapted to the setting, the benefits of a digital ED history taking tool could assist nurse-led triage in the waiting room and/or assessment and treatment by ED physicians.…”
Section: Introductionmentioning
confidence: 99%